Characteristics of music teachers that influence secondary music students' music learning / Katrine Malim - Malim, Katrine (Faculty of Music, 2013)
A study was conducted to investigate the characteristics of music teachers that influence secondary music students' music learning. This study adopted a quantitative method using the questionnaire as a means of data collection. Subjects were 116 students selected among Form 2 and Form 3 students from Sekolah Sultan Alam Shah, Putrajaya, SMK Rantau Panjang, Klang and SMK Section 19, Shah Alam. The result summarize that there are three highest means among each sections that the students choose which are item Teacher is interested in helping students learn ^=3.38), item Teacher uses blackboard or whiteboard in teaching (M=3.59) and item Teacher has good knowledge in music theory (M=3.51). These findings are important for music teachers and students to ensure the quality and quantity of teaching and learning music. This study provides a better understanding of the characteristics of a music teacher that can indirectly affect students' learning music. Recommendations for future research are also described in this study.